DAMPAK KEBERADAAN MINIMARKET IRIYANTI TERHADAP KELANGSUNGAN USAHA TOKO KELONTONG DI BANGKALAN - Aprilia, Multasiyeh; Septiana, Aldila (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
As the Indonesian economy progresses, the modern retail industry is increasingly transforming the existence of the traditional retail industry. Modern retail companies are causing traditional stores or grocery stores today to become more and more constricted. Located among grocery stores, Iriyanti Minimarket in Gebang Village offers both advantages and disadvantages. The purpose of this research is to find out how the existence of the Iriyanti minimarket affects the survival of the grocery store industry in Bangkalan district. This research uses qualitative descriptive techniques. Techniques to obtain data using interviews and observation techniques. The research informant is a four-man grocery store owner. For data analysis use the qualitative analysis method described in detail. Data analysis is reduction, data presentation, and conclusion drawing. Research findings show that minimarket envy has a positive and negative impact on the business of grocery stores. There has been a change in sales turnover as well as a decrease in the number of customers and also affects the quality of grocery stores that only sell retail goods. Besides, the strategy of the grocery store business owner to maintain the existence of the business is still unseen and is still very minimal.